P210 Which symptoms prompt patients with an exacerbation of COPD to persevere, self-treat or seek care? A comparison with health professionals. (2nd December 2011) - Wilson, J S; Sittlington, J J; McCrum-Gardner, E; Kee, F; Elborn, J S
Abstract : Introduction and Objectives: Exacerbations of Chronic Obstructive Pulmonary Disease are a major cause of morbidity and mortality. Despite the increased healthcare utilisation involved in treatment, little is known about how patients recognise an exacerbation. This study aims to identify the signs and symptoms that prompt patients to seek medical attention and also to identify which signs and symptoms health professionals expect patients to consider. Methods: A Factorial Survey was used to create clinical vignettes describing a variety of signs and symptoms of an exacerbation. A total of 30 patients with Chronic Obstructive Pulmonary Disease (mean %FEV1 38.9) and 47 health professionals (14 GPs, 19 Specialist Nurses and 15 Respiratory Consultants/Registrars) completed a unique random set of vignettes. A total of 600 patient and 960 health professional vignettes were analysed using multiple regression analysis. Results: There are substantial variations in the symptoms which patients regard as important prompts for action, compared to health professional expectations. Patients rely mainly on the colour and purulence of sputum (p<0.001) as a cue for all possible actions, whereas health professionals expected patients to consider a variety of symptoms. Conclusion: Many symptoms health professionals regard as important are not used to by patients to guide their decisions. As there is increasing focus on patients self-managing their disease, health professionals should exploit the symptoms patients already rely on rather than trying to change their behaviour.